العوامل المؤثرة على اختيار الطالب لمهنة التمريض - داؤد, نسرين (Latakia University Journal -Medical Sciences Series, 2017)
إن تنمية وتطوير مهنة التمريض ومعالجة النقص المستقبلي في القوى العاملة فيها يعتمد بشكل كبير على القدرة على جذب الشباب إليها، ولجذب هؤلاء الشباب يجب بدايةً التعرف على أهم الأسباب و العوامل التي قد تؤثر في اختيارهم لها. تهدف هذه الدراسة إلى تحديد العوامل المؤثرة على اختيار الطالب لمهنة التمريض. أجري البحث على عينة قوامها 250 طالب من طلاب السنة الأولى في كلية التمريض في جامعة تشرين. تم اعتماد منهج البحث الوصفي واستخدم الاستبيان كوسيلة لجمع البيانات. أظهرت النتائج أن معظم الطلاب ينظرون للتمريض على أنه عمل إنساني. 60% منهم اختاروا كلية التمريض كرغبة أولى. من أكثر الأسباب التي دفعتهم لدخول مهنة التمريض الرغبة في تقديم الرعاية للآخرين (72،8%). كان للأهل التأثير الأكبر في قرار دخولهم الكلية. كانت كلية التمريض المصدر الأول التي لجأ لها الطلاب خلال بحثهم عن معلومات عن التمريض. نصف المشاركين تقريباً أبدوا الرغبة في العمل في مهنة التمريض بعد التخرج و(40%) قرروا متابعة الدراسات العليا.Development of the nursing profession and address future shortages in the labor force depends largely on the ability to attract young people to enter it, to attract these young people, it should start to identify the important factors that influence their choice of nursing profession. The study aims to identify factors influencing choice of students for the nursing profession. Research was conducted on a sample of 250 students(first-year) in Nursing College atTishreen University. Descriptive research methodologywas followed and questionnaire to collect data was used. Most of student perceived nursing as humanitarian job, 60% of them selected nursing as their first choice. For most students (72.8%), the main reason they chose to study nursing is the desire to help others. They were mostly motivated by their parents to join nursing. Nursing College was the first source of information of nursing. Nearly half of the students made the decision to workin nursing after graduationand (40%) decided to pursue higher education,